Surface reconstruction in core@shell nanoalloys: Interplay between size and strain. (1st August 2022) - Settem, Manoj; Kumar, Pranav; Adlakha, Ilaksh; Kanjarla, Anand K.
Graphical abstract: Abstract: Shell structure in core@shell nanoalloys is studied where the core comprises of smaller atoms and covered by a thin shell with larger atoms. Mismatch strain, due to the size difference between core and shell atoms, plays a key role in determining the shell arrangement. Binary alloy systems having a wide range of lattice mismatch are considered which include Ni-Ag, Co-Ag, Cu-Ag, Co-Pt, Ni-Pd, Rh-Au, and Ni-Cu. Beginning from very small sizes, transformations in the shell structure are sketched out up to large sizes of ∼ 12 nm. These changes are accompanied by reconstruction of {100} facets in the shell to pseudo hexagonal (p-Hex) surfaces. Results show that p-Hex reconstruction occurs in specific size windows. The stability regime and the fraction of p-Hex surfaces is strongly dependent on the lattice mismatch. Comparison of p-Hex and {111} surfaces reveal significant atomic pressure differences. Finally, shells that are thicker than a monolayer are considered and it is found that p-Hex reconstruction is favored in thicker shells as well.